ANALISIS TRANSAKSI AKAD ISTISHNA’ PADA DEVELOPER PERUMAHAN SYARIAH AHSANA PROPERTY SYARIAH TUBAN - Putri, Silvia; Nuriyah, Khofifah; Fauzi, Muchamad (Brainy: Jurnal Riset Mahasiswa, 2024)
This study aims to find out how the flow of house buying and selling transactions is implemented by the Ahsana Property Sharia Developer in Tuban Regency. This type of research is descriptive qualitative research using data collection methods by conducting interviews, observation notes, and documents related to solving existing problems. The results of this study are that the contract used is an istishna’ contract free from usury or interest, also adheres to the concept of no fines, no confiscations, no bank mortgages (KPR), no BI Checking and no vanity contracts but pure deliberation. There is a guarantee and an installment system according to the agreement between the seller and the buyer.